Comparison of Titanium versus Resorbable Intramedullary Nailing in Pediatric Forearm Fractures - Ádám László Dávid; Flóra Mucsina; Eszter Antal; Anna Gabriella Lamberti; Aba Lőrincz; Gergő Józsa (MDPI AG, 2024)
Pediatric forearm fractures, particularly involving the shaft or diaphysis, are common injuries typically resulting from accidental trauma during various activities. Traditional treatment involves closed reduction and casting; however, surgical intervention may be necessary in certain cases. The gold standard surgical approach utilizes elastic stable intramedullary nailing (ESIN), but a newer technique uses bioabsorbable intramedullary nails made of poly(lactic-co-glycolic acid) (PLGA). This study aims to compare the outcomes of these two surgical methods in pediatric diaphyseal forearm fractures. We retrospectively reviewed 86 patients who underwent operative treatment due to the diaphyseal fractures of the forearm in the Surgical Division, Department of Pediatrics, Medical School, University of Pécs, Pécs, Hungary between 2018 and September 2022. The mean age was 9.48 (ranging from 4 to 17). A total of 41 patients underwent surgery with PLGA implants (RESIN technique), while 45 patients were treated with titanium elastic nails (ESIN technique). Various factors including patient demographics, injury mechanisms, fracture characteristics, and complications were assessed. Both groups showed similar gender distribution, with a majority of fractures occurring in boys (the male-female ratio was 31:10 in the PLGA group, while in the titanium elastic nailing (TEN) group, this ratio was 29:16, with no statistical difference between the groups (p > 0.005). The average age of the patients treated with PLGA implants (8.439 years) was lower compared to those treated with titanium nails (10.422 years). A statistically significant difference was found regarding the average age of the two groups (p = 0.0085). Left-sided injuries were more prevalent in both groups (59% of the cases in the PLGA group and 69% in the TEN group, with no statistically significant difference, p = 0.716), and fractures typically involved both the radius and ulna. This represents 93% of the cases in the PLGA group and 80% in the TEN group. Regarding the involvement of bones, we also did not find a statistically significant difference (p = 0.123). The mechanisms of injury predominantly involved indirect force, such as falls (30 cases in the PLGA group and 27 cases in the TEN group), and no statistically significant difference was found (p = 0.139) regarding the mechanism of the injury. Complication rates were lower in the PLGA group (7%) compared to the titanium group (20%). The treatment of pediatric diaphyseal forearm fractures using PLGA implants appears to be a viable alternative to traditional titanium implants. Advantages include no need for secondary surgery and associated cost savings and reduced complication rate and stress associated with anesthesia and surgery. Prospective randomized trials are warranted to further validate these findings and explore long-term outcomes.